Technical Efficiency of Farming Business to Optimize Rice Production (Oryza Sativa L.): The Case in Pajawanlor Village, Ciawigebang District, Kuningan Regency - Andri Priyatna; Heru Supriatna; Tyas Tony Taufik; Achmad Faqih; Yayat Rahmat Hidayat (Riviera Publishing, 2025)
This research examines the technical efficiency of rice farming (Oryza sativa L.) in Pajawanlor Village, Ciawigebang District, Kuningan Regency, to assess efficiency levels and identify influencing factors. Utilizing a quantitative research approach, the study employs the Cobb-Douglas Stochastic Frontier Production Model alongside the Maximum Likelihood Estimation (MLE) method to analyze data from 35 rice farmers. The findings reveal an average technical efficiency level of 75%, indicating that farmers could boost their production by 25% through optimized resource utilization. Key factors affecting efficiency include land, seeds, fertilizers, labor, and farming experience. These results underscore the importance of targeted interventions, such as improved input management, better access to agricultural technology, and training programs to enhance farmers' efficiency. The implications of this research extend to policy recommendations aimed at increasing rice productivity and ensuring food security, particularly in rural agricultural contexts. Stakeholders—policymakers, agricultural extension officers, and farmers—can devise more effective strategies for optimizing rice farming outcomes by addressing technical inefficiencies.